Report of the Working Group on Small Scale Sector, Administrative Reforms Commission - Planning Commission (Planning Commission, 1968)
The Administrative Reforms Commission had set up a Working Group on Small Scale Sector on 31-7-1967 with the following objectives in view:.— (i) to examine the efficacy of the several steps taken by the Central and the State Governments for the encouragement of the Small Scale Sector; (ii) to suggest a clear demarcation of responsibilities between the Central Government and the State Governments so as to remove organisational bottlenecks; (iii) to indicate the proper role and functions of the Central Small Industries Organisation; (iv) to suggest an appropriate organisational pattern for providing the various inputs like finance, raw materials, etc. to the small scale sector; and (v) to examine the possibility of providing legislative protection to the small scale industry.
Report of the Working Group on Small Scale Sector
Planning Commission Library Government of India